Health Issues in Women with Multiple Sclerosis - Houtchens, Maria K.; Sadovnick, A. Dessa (Springer Vienna : Imprint: Springer, 2017)
This book addresses specific concerns of females affected by multiple sclerosis, where women are disproportionally impacted by the disease. MS is an autoimmune disease of the central nervous system affecting young adults of reproductive age. This book presents the current understanding of genetic variables, hormonal influences, immunological milieu and neurological outcomes, discussing issues such as fertility, pregnancy management, and menopause, as well as end of life care and mortality in women with MS. With contributions by international experts, this interdisciplinary book will serve as a useful reference and guide for MS specialists, general neurologists, obstetricians/gynecologists, physicians in training, family practice doctors, clinical nurse specialists in multiple sclerosis, and all other healthcare professionals involved in the care and treatment of women affected by MS.
Keywords: Medicine.; General practice (Medicine).; Obstetrics.; Neurology.; Nursing.; elektronické knihy; electronic books